SYSTEMATIC LITERATURE REVIEW: DAMPAK OUTDOOR LEARNING TERHADAP PEMBELAJARAN IPAS DI SEKOLAH DASAR - Aliyah, Siti; Novi Yuliyanti; Dedi Romli Triputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Natural and Social Sciences (IPAS) learning in the Merdeka Curriculum emphasizes contextual, meaningful, and student-centered learning. One of the learning approaches considered effective in supporting these objectives is outdoor learning, which utilizes the surrounding environment as a learning resource. This study aims to analyze the impact of the outdoor learning method on students' learning outcomes, motivation, engagement, and learning experiences based on findings from previous studies. The research employed a literature review method by collecting and analyzing various scientific sources, including journal articles, books, and other publications relevant to the research topic. The findings indicate that the implementation of outdoor learning has a positive impact on IPAS learning, including improving students' learning outcomes, conceptual understanding, learning motivation, active participation, critical thinking skills, science process skills, collaboration skills, and environmental awareness. Learning activities conducted outside the classroom also provide more meaningful learning experiences, as students are able to relate IPAS concepts to real-life phenomena found in their surrounding environment. Furthermore, outdoor learning supports the implementation of active, innovative, and enjoyable learning in accordance with the principles of the Merdeka Curriculum. Therefore, outdoor learning can be considered an effective instructional approach to enhance the quality of IPAS learning in elementary schools.